Preserving the reproductive potential of transgender and intersex people. (2nd January 2018) - Rowlands, Sam; Amy, Jean-Jacques
Abstract: Background: The bodies of some transgender and intersex people have been mutilated and their minds subjected to immense distress. Their gender has often been determined by others. Loss of fertility used to be considered an inevitable consequence of treatment. Objective: To review the issue of preserving the reproductive potential of transgender and intersex people. Methods: A narrative review based on a wide-ranging search of the literature in multiple disciplines. Results: Major technological advances have facilitated reproduction for transgender and intersex people in the last few years. A majority of trans-adults believe that fertility preservation should be offered to them. Deferment of surgery for intersex people is often best practice; gonadectomy in infancy closes off fertility options and determines a gender they may later regret. Conclusions: Transgender and intersex people should be able to consent to or decline treatment, especially radical surgery, themselves. Preservation of reproductive potential and sexual function must be given a high priority. Treatment by multidisciplinary teams can provide a strong emphasis on mental health and well-being. Detailed information about options, an absence of any coercion and enough time are all needed in order to make complex, life-changing decisions.